The Analysis of the Contribution of the Southwestern Indian Ocean Tropical Cyclones (TCs) to December, January, February, March (DJFM) Rainfall Season over Tanzania - Kai, Kombo Hamad; Shaghude, Yohanna Wilson; Osima, Sarah E; Kijazi, Agnes Laurent; Uiso, Christian CBS; Nyenzi, Burhan (European Journal of Applied Sciences, 2022)
The contribution of Southwestern Indian Ocean (SWIO) Tropical cyclones (TCs) to the December to March (DJFM) rainfall season over Tanzania was analyzed. Seasonal, monthly and daily rainfall data were obtained from Tanzania Meteorological Authority (TMA), while data for sea surface temperatures (SSTs), relative and specific humidity, zonal and meridional winds were acquired from NOAA (NCEP – NCAR). Tropical Rainfall Measuring Mission (TRMM) daily average gridded rainfall estimates were used. The observed and gridded rainfall data for each TC day were extracted and computed to monthly and seasonal totals for all TCs and non TCs days. Correlation between DJFM TCs and DJF/DJFM rainfall were determined. Inter annual variability between TCs and DJF rainfall was analyzed. Wind patterns at 850 - 200 mb, relative humidity (850-700mb), vertically integrated horizontal wind and moisture divergence (1000-500 mb) for two TC events (Izilda and Fobane) were analyzed. The results revealed that, TCs contribution to the DJFM rainfall was very significant. The influence of TCs to monthly total rainfall showed a general increasing trend from north to south along the coast of Tanzania, with a southwest to northeast alignment. On the other hand correlation between DJFM TCs with DJF rainfall was relatively weak at some stations while few stations including Dodoma and Tabora were showing relatively higher correlations of about 0.39 (p ≤ 0.05) suggesting that these stations are highly vulnerable to the TCs impacts. Moreover, results had shown that the distribution of TCs rainfall prone areas run from southern parts (Mtwara) through central parts (Dodoma) to northeastern highlands (Kilimanjaro). Analyses revealed that 700 mb wind vectors, integrated moisture fluxes and their convergence from Congo air mass, northwesterly and northeastern Indian Ocean air masses were the main contributors of rainfall over Tanzania during TCs events. Conclusively, the study showed that TCs has significant contribution to the DJF and DJFM rainfall in Tanzania, thus more studies for understanding the dynamic of TCs in relation to rainfall is required for improving the weather forecasts in Tanzania.